Microbial and chemical dynamics during marula fermentation - Phiri, Archie (My University, 2018)
Refer to the document
Thesis (MSc. (Microbiology)) --University of Limpopo, 2018
Keywords: Marula wine; Fermentation; Sclerocarya birrea; Fermentation; Brewing; Microbiological chemistry